Informational Shocks and Street-Food Safety: A Field Study in Urban India - Gianmarco Daniele; Sulagna Mookerjee; Denni Tommasi (Institute of Labor Economics (IZA), 2020)
The street food market is a major source of food in developing countries, but is often characterized by unsafe food conditions. We investigate whether improvements in food safety can be achieved by providing information to vendors in the form of a training. Among randomly assigned groups of street-food vendors in Kolkata, India, we find large improvements in knowledge and awareness, but little change in their observed behavior. We provide two main explanations for these findings. First, information acquisition by itself does not make it significantly easier for vendors to provide customers with safer food options. Second, although consumers in this market have a positive willingness to pay for food that is perceived as more hygienic, they struggle to distinguish between safe and contaminated food. We conclude that information to vendors is not the key constraint in this context, and that policies mitigating supply-side constraints as well as improving food safety awareness among consumers are likely to have more impact.
Keywords: O12; O17; 330; food safety; public health; street-food; hawkers; trainings; RCT; informal sector